2019
DOI: 10.1096/fj.201802430r
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects of low‐intensity exercise on cancer cachexia–induced muscle atrophy

Abstract: We hypothesized that low‐intensity endurance exercise might be more effective in preventing cancer cachexia–induced muscle atrophy through both an increase in protein synthesis and a decrease in protein degradation. The purpose of present study was to evaluate the effects and to clarify the mechanism of low‐intensity endurance exercise on cancer cachexia–induced muscle atrophy. Twenty‐four male Wistar rats were randomly divided into 4 groups: control (Cont), Cont plus exercise (Ex), AH130‐induced cancer cachex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 48 publications
0
38
0
Order By: Relevance
“…Furthermore, some previous studies revealed that autophagic proteolysis is involved in cancer cachexia-induced muscle atrophy [9][10][11]. In contrast, the expression of molecules related to protein synthesis, including insulin-like growth factor 1 (IGF-1) and phosphorylated mechanistic target of rapamycin (mTOR), is suppressed in cachectic muscles [12]. It was also demonstrated that redox homeostasis balances protein synthesis and degradation in skeletal muscles during cancer cachexia [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some previous studies revealed that autophagic proteolysis is involved in cancer cachexia-induced muscle atrophy [9][10][11]. In contrast, the expression of molecules related to protein synthesis, including insulin-like growth factor 1 (IGF-1) and phosphorylated mechanistic target of rapamycin (mTOR), is suppressed in cachectic muscles [12]. It was also demonstrated that redox homeostasis balances protein synthesis and degradation in skeletal muscles during cancer cachexia [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…There are several protective and therapeutic measures against muscular atrophy, such as intake of essential amino acids (8), insulin-like growth factor (IGF)-I treatment (9) and anabolic androgenic steroids (10); however, these measures can cause increased drug resistance and cardiac events, limiting their therapeutic utility for the treatment of muscle atrophy (4,11). Although major advances in our understanding of protein loss in muscle atrophy have been made recently (1215), it is important to elucidate the underlying molecular regulatory mechanisms of dysfunctional muscle anabolism during skeletal muscle atrophy, in order to develop promising strategies to prevent and treat muscular atrophy.…”
Section: Introductionmentioning
confidence: 99%
“…in contrast, resistance training induced the expression of genes related to muscle damage and repair, such as myogenin and iGF-ieb, which might be due to the excessive stress caused by the high resistance load in the tumor-bearing state (147). in addition, Tanaka et al (148) discovered that low-intensity exercise inhibited Yoshida aH130 ascites lc cell-induced cancer cachexia through the skeletal uPS in male Wistar rats. in addition, low-intensity exercise increased the levels of hypoxia-inducible factor-1α and p-aMPK, which suppressed the loss of muscle mass and the inactivation of mTor in the soleus muscle.…”
Section: Treatment Of Muscle Atrophy Caused By Cancer Cachexiamentioning
confidence: 99%